Systematics and phylogeny of Cristacoxidae (Copepoda, Harpacticoida): a review - Huys, Rony; Kihara, Terue Cristina (Zootaxa, 2010)
Both sexes of a new species of Noodtorthopsyllus Lang, 1965 (Harpacticoida, Cristacoxidae) from a sandy beach in São Paulo State (Brazil) are described using light and scanning electron microscopy. Noodtorthopsyllus tageae sp. nov. displays a mosaic of characters drawn from both Noodtorthopsyllus and Cristacoxa Huys, 1990, blurring the boundaries between both genera. Consequently, Cristacoxa, the type genus of the nominal family-group taxon Cristacoxidae Huys, 1990, is relegated to a junior subjective synonym of Noodtorthopsyllus, and its type species is transferred to the latter as N. petkovskii (Huys, 1990) comb. nov. A new genus Acuticoxa is proposed to accommodate A. ubatubaensis sp. nov. (type species), collected on the northern continental shelf of São Paulo State, and A. biarticulata sp. nov., previously identified as Laophontisochra sp., from the Northern Magellan Straits. Amended diagnoses are provided for Noodtorthopsyllus and Laophontisochra. Autapomorphies supporting the monophyly of the Cristacoxidae are re-evaluated, including new data on P3 endopod sexual dimorphism and caudal ramus development. It is concluded that a recently published hypothesis of a deeply rooted split of the family into two highly divergent lineages cannot be supported. Consequently, both Laophontisochra and Acuticoxa gen. nov. are removed from the Cristacoxidae and tentatively assigned to the Nannopodidae (ex Huntemanniidae), forming a clade with three other genera displaying coxal modifications on leg 1 (Rosacletodes Wells, 1985; Huntemannia Poppe, 1884; and an as yet undescribed genus from Brazil). Based on the sexual dimorphism of the P4 endopod, we propose to transfer Metahuntemannia Smirnov, 1946 and Pottekia Huys, 2009 from the Nannopodidae to the Canthocamptidae (subfamily Hemimesochrinae) where they are probably most closely related to Psammocamptus Mielke, 1975; Bathycamptus Huys & Thistle, 1989; Perucamptus Huys & Thistle, 1989; and Isthmiocaris George & Schminke, 2003. An identification key to the genera of the Nannopodidae is presented.